Complications du Diabète en Côte d’Ivoire chez les Patients Diagnostiques Tardivement - Adjoua Yeboua Florence Kouakou; Adama Kamagaté; Angoué Paul Yapo (European Scientific Journal, ESJ, 2016)
Diabetes is a metabolic disorder that affects more and more all social classes. According to the literature this disease have many causes, but some type of diabetes such as Type 2 diabetes is the most linked to a metabolic disorder due to abdominal obesity. To better understand diabetes and its complications, we studied diabetes and its complications in patients who were hospitalized urgently. Our study showed that 95.80% of hospitalized diabetics are type 2 against 3.36% type 1. Among diabetics, there are 56.04% men and 43.86% women. But the rate of abdominal obesity was 60.50% for both men and women. This study also indicated that 60.63% of hospitalized diabetics suffer of macrovascular complications, against 39.27% of microvascular complications. Also patients with macrovascular complications suffer specifically from coma, diabetic foot, amputations, stroke; and those with microvascular complications suffer specifically from erectile dysfunction, chronic renal failure, polyneuropathy, lung infections, and also comas. Our study has shown that many patients are unaware of their diabetic condition before the acute complications of diabetes, which is alarming. So we get on the alarm that measures are taken to reduce the complications of diabetes in Ivory Coast.